Age and Body Anthropometry as Predicting Factors for Carpal Tunnel Syndrome among Egyptian Obese Women - Zaki, Moushira; Ali, Maha; Yousef, Walaa; Ezzat, Wafaa; Basha, Walaa (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Carpal tunnel syndrome (CTS) is the most prevalent entrapment neuropathy in the upper limb. The most consistent risk factors are female gender, age, and obesity. The results of previous studies are conflicting, and moreover, data from studies regarding obesity and nerve conduction velocity are not available for our Egyptian population. AIM: This study was designed to investigate the contribution of age and body anthropometry as predictor factors to the CTS and to identify patients at high risk for CTS among Egyptian obese women. METHODS: The study included 120 obese women grouped according to the clinical and electrodiagnostic (EDX) findings into two groups: 60 with CTS and 60 without CTS (non-CTS). EDX study was used in the diagnosis of median nerve entrapment at the level of the wrist, according to the American Association of Neuromuscular and EDX Medicine. Body weight and height were measured and then body mass index (BMI) was calculated. Waist-to-hip ratio (WHR) was determined from the measured waist circumference (WC) and hip circumference (HC). Mid upper arm circumference (MUAC) was measured as well. The receiver operating characteristic (ROC) curve was used to assess the power of age and body anthropometry as predictor factors for CTS. RESULTS: CTS obese cases showed significantly lower values of both median motor nerve conduction velocity (MMNCV) and median sensory nerve conduction velocity compared to those without CTS. Significantly higher median sensory latency and median motor latency have been found in CTS cases compared to non-CTS group. Significant differences in the mean age have been found between the two groups and a tendency for higher body anthropometry measures in the CTS cases relative to those without CTS. Moreover, there were negative correlations between MMNCV and obesity indices. Age showed the highest area under the ROC curve, followed by BMI, WHR WC, HC, and MUAC. CONCLUSION: Age and obesity indices are important risk factors that can be used as predictors to CTS in obese women. Age is a more powerful diagnostic tool relative to the anthropometric measurements. Women of age above 40 years and suffering from a high degree of obesity are at risk of developing CTS.